EFFECT OF PLANTS MEAL FROM Eeichhornia crassipes AND Salvinia molesta ON GROWTH OF Pangasius sp. - Retno Cahya Mukti; Ria Octaviani (University of Lampung, 2020)
Plant meals from Eichhornia crassipes and Salvinia molesta can be used as alternative ingredients for feed in aquaculture. The purpose of this study was to determine the effect of the use of plant meals as a feed on the growth of Pangasius. The experimental designed consist of three treatments and triplicates: P0: commercial feed (control); P1: feed with the addition of 25% Eichhornia crassipes; P2: feed with the addition of 25% Salvinia molesta. The results showed that plant meals in feed showed significantly different results on the growth of body weight, specific growth rate, and efficiency of Pangasius feed. The recommended treatment was the addition of Salvinia molesta with a weight growth value of 3.84 g, a specific growth rate of 2.07%, and feed efficiency of 59.96%.